Finnish National Esophago-Gastric Cancer Cohort (FINEGO) for studying outcomes after oesophageal and gastric cancer surgery: a protocol for a retrospective, population-based, nationwide cohort study in Finland - Joonas H. Kauppila; Pasi Ohtonen; Tuomo J. Karttunen; Arto Kokkola; Simo Laine; Tuomo Rantanen; Ari Ristimäki; Jari V. Räsänen; Juha Saarnio; Eero Sihvo; Vesa Toikkanen; Tuula Tyrväinen (BMJ Publishing, 2022)
Introduction: Surgery for oesophageal and gastric cancers is associated with high morbidity, mortality and poor quality of life postoperatively. The Finnish National Esophago-Gastric Cancer Cohort has been established with the aim of identifying factors that could contribute to improved outcomes in oesophago-gastric cancer.
Methods and analysis: All patients with oesophageal and gastric cancer diagnosed in Finland between 1987 and 2015 will be identified from the Finnish national registries. The Finnish Cancer Registry and Finnish Patient Registry will be used to identify patients that fulfil the inclusion criteria for the study: (1) diagnosis of oesophageal, gastro-oesophageal junction, or gastric cancer, (2) any surgical treatment for the diagnosed cancer and (3) age of 18 or over at the time of diagnosis. Clinical variables and complication information will be retrieved in extensive data collection from the medical records of the relevant Finnish hospitals and complete follow-up for vital status from Statistics Finland. Primary endpoint is overall all-cause mortality and secondary endpoints include complications, reoperations, medication use and sick leaves. Sub-studies will be implemented within the cohort to investigate specific populations undergoing oesophageal and gastric cancer surgery. The initial estimated sample size is 1800 patients with surgically treated oesophageal cancer and 7500 patients with surgically treated gastric cancer.
Ethics and dissemination: The study has been approved by the Ethical Committee in Northern Ostrobothnia, Finland and The National Institute for Health and Welfare, Finland. Study findings will be disseminated via presentations at conferences and publications in peer-reviewed journals.